Invasive alien plants and rural livelihoods: a case of Gwanda District, Zimbabwe - Dube, Nqobizitha (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
Biodiversity is the cornerstone of ecosystem functioning and the realisation that most rural African community livelihoods are directly dependent on ecosystem goods and services warrants its conservation. Invasive alien plants threaten biodiversity and compromise the ecosystem's ability to provide goods and services for rural communities, thereby negatively affecting livelihood strategies. Information on IAPs is lacking in most African countries, thus, the livelihood effects of Invasive Alien Plants (IAPs) are not clearly understood. In Zimbabwe, Cylindropuntia fulgida var. fulgida (Cff) has invaded Gwanda district in the Matabeleland south province compromising local household capital assets that contribute to livelihood strategies and altering the ecosystem. This study exposed the rural worldview of the environment, the effect that Cff has on local livelihood strategies and the effectiveness environmental management institutions in rural Gwanda district. The study followed a post positivist paradigm. The impacts of IAPs on rural communities in Zimbabwe were analysed by looking at the livelihood stresses that arise because of Cff. The research used multi-stage sampling to select a representative sample of respondents. Primary data was collected using semi-structured questionnaires, group discussion and key informant guides. Furthermore, document analysis was conducted to collect secondary data. The data analysis process used Computer packages Microsoft Excel, SPSS and NVIVO. Results showed that livelihood benefits that species in the natural environment provide strongly influence environmental perceptions of rural African communities. Additionally, the study showed that Cff compromises the local ecosystem and reduces its ability to support the dominant livelihoods in the study area. The long-term result of such a situation in the absence of control is increased poverty and the failure to realise sustainable development. However, results indicated that IAPs could also improve the poverty situation of a community before they have reached the threshold points. It is therefore imperative to know the threshold points of an invasive plant in order to ascertain the efficient point to intervene. The study also showed that benefits of invasive plants accrue to different members of a society at different times (private/public). This knowledge allows the adoption of efficient and effective control strategies.
Keywords: Cylindropuntia fulgida; Invasive plants -- Economic aspects; Invasive plants -- Control; Invasive plants -- Economic aspects -- Zimbabwe; Ecosystem services -- Zimbabwe; Environmental policy -- Zimbabwe; Ecosystem management -- Zimbabwe; Cactus -- Economic aspects -- Zimbabwe